Nurturing future women TVETpreneurs : A study on female TVET students’ entrepreneurial intentions - Wendy Teoh, Ming Yen; Tan, Lay Hong; Omar, Siti Sarah; Chong, Siong Choy; Chong, Chin Wei (SHPMedia Sdn Bhd, 2025)
The Malaysian government’s commitment to Technical and Vocational Education and Training (TVET) is crucial for promoting economic growth and reducing youth unemployment, particularly among women. Recognizing female TVETpreneurship as a pivotal pathway for economic empowerment and gender equality, this study aims to investigate the factors that influence female TVET students’ entrepreneurial intentions. Based on the 104 female TVET students who participated in this study, the results indicate that role models, digital literacy, technology adoption, and access to resources are significant factors influencing female TVET students’ entrepreneurial intentions, irrespective of whether they have taken formal entrepreneurship courses. The findings contribute to the existing body of literature and offer practical recommendations for TVET institutions, policymakers, and society. By equipping female TVET students with essential digital, technical, and entrepreneurial skills, this study contributes to Malaysia’s long-term economic and social development, paving the way for a more inclusive and sustainable future for women.